PERSEPSI MENGENAI SKANDAL AUDITOR TERHADAP PILIHAN KARIER SEBAGAI AUDITOR - Satrio, Arif Budi (MABIS, 2013)
Auditor profession have come to be society focus in the last few years, especially when case of Enron in American up to case.Auditors scandals become problem, especially to accountingÂ students that want to start their carrier. So that, this research is to examined and analyze auditorâs scandals affect opinion, work at accounting profession, and career plan of accounting students. Data was collected by filling in questionnaire. Sample taking technique used in the research was purposive sampling, with criterion that is, the students of accounting department which still or finished taking audit studying objects at Pontianak. Data was analyzed by SPSS version 16 software package. This research includes three hypotheses. From three hypotheses, all of hypotheses are accepted. The result of testing hypothesis suggests that there is no significant auditorâs scandals influence on the student career choice for the auditor. This research is support previous research conducted by Wirianata in which students perceive positive accounting profession post-Enron scandals.